Preparation method of large-thickness organic solar cell based on multi-layer coating

By diluting the solution and scraping multiple times to prepare the active layer of the organic solar cell, the problem of uneven active layer when preparing large-thick organic solar cells is solved, and the energy conversion efficiency of the device is significantly improved.

CN119421624AInactive Publication Date: 2025-02-11SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510005312.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when preparing large-thick organic solar cells in the scraping method, the active layer is easily uneven due to material solubility limitation, which affects device performance.

Method used

The photosensitive active layer in the thickness range of 100-500 nm was prepared by diluting the solution and using multiple scraping methods to improve the uniformity and crystallinity of the active layer.

Benefits of technology

The filling factor uniformity of organic solar cells and the crystallinity of the active layer are significantly improved, and the energy conversion efficiency is improved, making it at the leading level among organic solar cells prepared by halogen-free solvent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421624A_ABST
    Figure CN119421624A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a large-thickness organic solar cell based on multilayer coating, and belongs to the technical field of solar cell device preparation. The active layer with the thickness ranging from 100 nm to 500 nm is prepared through a method of diluting a solution and coating for multiple times. Wherein the crystallinity of the active layer prepared by multiple times of spin coating is obviously reduced, adverse effects on the performance of the organic solar cell are caused, the uniformity of the active layer prepared by multiple times of blade coating is greatly improved, and the molecular crystallization is obviously enhanced. The uniformity of the filling factors of the active layer prepared by diluting the solution and performing blade coating twice is greatly improved, and the energy conversion efficiency of the organic solar cell with the active layer thickness of 500nm is at a leading level in devices prepared by processing a halogen-free solvent at present.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cell device preparation, and in particular relates to a method for preparing a thick organic solar cell based on multi-layer coating. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, thanks to the development of new materials, especially the synthesis of non-fullerene acceptor materials and device optimization strategies, organic solar cells (OSCs) have made significant progress. The energy conversion efficiency of single-junction small-area solar cells has reached 20%, showing great application potential. With the continuous improvement of the performance of small-area OSCs in the laboratory, the development of high-efficiency devices with thick active layers that are compatible with large-scale preparation is an important step on the road to commercialization. The optimization of the active layer thickness involves the balance between exciton diffusion and charge generation, transport and extraction. Increasing the thickness of the active layer helps to improve photon absorption and generate more carriers, but it also increases the possibility of carrier recombination, which requires careful optimization to improve device performance. Scrape coating has been widely used in the preparation of organic solar cells due to its low material waste, suitability for roll-to-roll processes, and high-throughput continuous processing. Compared with spin coating, scrape coating can save more materials; compared with slit coating, scrape coating is more convenient, and can be used to prepare small-area batteries, and is also suitable for large-area coating. When scraping thick organic solar cells, the method of increasing the concentration of the active layer solution is usually used to scrape it once, but this method is limited by the solubility of the organic material, and it is easy to cause the non-uniformity of the active layer film, which has a significant impact on the micro-nano structure of the active layer. Because scrape coating involves more complex fluid dynamics processes, its nucleation and crystallization process lacks effective regulation, and the energy conversion efficiency of the resulting organic solar cells still lags behind that of organic solar cells prepared by spin coating.

[0004] Therefore, it is crucial to explore the scraping method to prepare efficient and uniform device structures of thick organic solar cells. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a thick organic solar cell based on multi-layer coating. The present invention prepares a photosensitive active layer with a thickness range of 100-500 nm by diluting a solution and applying multiple scrapings. The uniformity of the filling factor of the prepared organic solar cell is greatly improved.

[0006] In order to achieve the above object, the technical solution of the present invention is: The first aspect of the present invention provides a thick organic solar cell based on multi-layer coating, which structurally comprises: conductive glass, a hole transport layer, an active layer, an electron transport layer and a metal electrode; The thickness of the active layer is 100-500 nm.

[0007] In some embodiments of the present invention, the conductive glass is indium tin oxide conductive glass, the hole transport layer material is PEDOT:PSS, the donor of the active layer material is PM6, the acceptor is L8-BO, the donor-acceptor mass ratio is 1:1.1-1.3, the electron transport layer material is PNDIT-F3N-Br, and the metal electrode is a silver electrode.

[0008] The second aspect of the present invention provides a method for preparing the aforementioned thick organic solar cell based on multilayer coating, comprising the following steps: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; In an air atmosphere, the active layer material is scraped on the hole transport layer multiple times, the concentration of the active layer material solution is 8-20 mg / mL, the scraping speed is 10-45 mm / s, the amount of liquid dropped once is 20-90 μL, the substrate temperature is 40-100°C, and the active layer with a thickness range of 100-500 nm is obtained; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a cathode is prepared on the electron transport layer to obtain a thick organic solar cell based on multilayer coating.

[0009] In some embodiments of the present invention, the conductive glass is indium tin oxide conductive glass, which is ultrasonically cleaned with deionized water, acetone, anhydrous ethanol and isopropanol in sequence, blown dry with nitrogen, treated with ultraviolet light for 15-25 min, and then spin-coated to prepare a hole transport layer.

[0010] In some embodiments of the present invention, the hole transport material is PEDOT:PSS, and PEDOT:PSS is spin-coated on the surface of the conductive glass at a spin-coating speed of 3000-5000 rpm for 30-50 s, and annealed at 130-180°C for 10-20 min to obtain a hole transport layer.

[0011] In some embodiments of the present invention, when the active layer with a thickness of 100 nm is prepared by multiple scraping on the hole transport layer in an air atmosphere, the concentration of the active layer material solution is 9.9 mg / mL, the scraping speed is 30 mm / s, the amount of liquid dropped at one time is 30 μL, the substrate temperature is 80°C, and the scraping is performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 300 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 13.9 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 500 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 17.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; The scraping is performed 1-5 times, the second scraping direction is opposite to the first scraping direction, the third scraping direction is opposite to the second scraping direction, and so on.

[0012] In some embodiments of the present invention, the solvent of the active layer material solution is one of chloroform, o-xylene or toluene, the donor of the active layer material is PM6, the acceptor is L8-BO, and the donor-acceptor mass ratio is 1:1.1-1.3; After the scraping is completed, annealing is performed at 95-105° C. for 8-12 min in an inert atmosphere to obtain an active layer with a thickness ranging from 100 to 500 nm.

[0013] In some embodiments of the present invention, the method for preparing the electron transport layer comprises the following steps: Under nitrogen atmosphere, 0.5-1.5 mg / mL PNDIT-F3N-Br solution was spin-coated onto the active layer at a spin-coating speed of 2000-4000 rpm for 30-50 s.

[0014] In some embodiments of the present invention, the solvent of the PNDIT-F3N-Br solution is methanol.

[0015] In some embodiments of the present invention, the method for preparing the metal electrode comprises the following steps: Metal electrodes with a thickness of 80-100 nm were prepared on the electron transport layer by thermal evaporation under vacuum conditions.

[0016] In some embodiments of the present invention, the vacuum condition is 2.5×10 -4 -5×10 -4 Pa.

[0017] The beneficial effects of the present invention are: The present invention prepares an active layer with a thickness range of 100-500 nm by a method of diluting a solution and scraping multiple times, and the embodiments of the present invention also prepare an active layer with a thickness range of 100-500 nm by one or more spin coatings and one scraping. Compared with the active layer prepared by one spin coating, the active layer prepared by multiple spin coatings has a significantly reduced crystallinity, which has an adverse effect on the performance of organic solar cells. Compared with the active layer prepared by multiple spin coatings, the active layer prepared by the preparation method of multiple scraping coatings can enhance its crystallinity without destroying the orderly stacking of molecules. Compared with the active layer prepared by one scraping coating, the active layer prepared by multiple scraping coatings of the present invention has not only greatly improved uniformity, but also significantly enhanced molecular crystallization, and the advantage is still significant in the active layer with a thickness of 500 nm. The energy conversion efficiency of thick organic solar cells prepared by the method of the present invention is comparable to that of organic solar cells with the same active layer thickness prepared by one-time scraping, and the uniformity of the filling factor is greatly improved. The energy conversion of organic solar cells with an active layer thickness of 500 nm is at the leading level among the organic solar cells (14%) currently prepared by halogen-free solvent processing.

[0018] Compared with the common method of increasing the thickness of the active layer by increasing the solution concentration, the preparation method proposed in the present invention uses a diluted solution for multiple scraping, which reduces the limitation of the solubility of the organic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 This is a schematic diagram of preparing an organic solar cell based on multiple scraping in Example 1 of the present invention; Figure 2 This is a schematic diagram of preparing an organic solar cell based on multiple spin coating in Comparative Example 1 of an embodiment of the present invention; Figure 3 The performance parameters of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1 of the present invention are summarized in a graph; wherein (a) is the energy conversion efficiency of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping, (b) is the fill factor of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping, (c) is the open circuit voltage of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping, and (d) is the short circuit current density of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping; Figure 4 The performance parameters of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1 of the present invention are summarized in a graph; wherein (a) is the energy conversion efficiency of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating, (b) is the fill factor of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating, (c) is the open circuit voltage of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating, and (d) is the short circuit current density of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating; Figure 5 The two-dimensional grazing incidence wide-angle X-ray diffraction pattern and one-dimensional integral curve of the active layer with a thickness of 500 nm prepared by one-time scraping and multiple scraping in Example 1 of the present invention; wherein, (a) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of the active layer with a thickness of 500 nm prepared by one-time scraping in Example 1, (b) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of the active layer with a thickness of 500 nm prepared by multiple scraping in Example 1, and (c) is a one-dimensional integral curve of the active layer with a thickness of 500 nm prepared by one-time scraping and the active layer with a thickness of 500 nm prepared by multiple scraping in Example 1; Figure 6 The two-dimensional grazing incidence wide-angle X-ray diffraction pattern and one-dimensional integral curve of the active layer with a thickness of 500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1 of the present invention; wherein, (a) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of the active layer with a thickness of 500 nm prepared by single spin coating in Comparative Example 1, (b) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of the active layer with a thickness of 500 nm prepared by multiple spin coating in Comparative Example 1, and (c) is a one-dimensional integral curve of the active layer with a thickness of 500 nm prepared by single spin coating and the active layer with a thickness of 500 nm prepared by multiple spin coating in Comparative Example 1; Figure 7The figures are atomic force microscopy images of active layers with a thickness of 100-500 nm prepared by one-time scraping and multiple scraping in Example 1 of the present invention; wherein, (a) is an atomic force microscopy image of an active layer with a thickness of 100 nm prepared by one-time scraping, Rq=1.26 nm; (b) is an atomic force microscopy image of an active layer with a thickness of 300 nm prepared by one-time scraping, Rq=1.30 nm; (c) is an atomic force microscopy image of an active layer with a thickness of 500 nm prepared by one-time scraping, Rq=1.35 nm; (d) is an atomic force microscopy image of an active layer with a thickness of 100 nm prepared by multiple scraping, Rq=0.86 nm; (e) is an atomic force microscopy image of an active layer with a thickness of 300 nm prepared by multiple scraping, Rq=1.04 nm; (f) is an atomic force microscopy image of an active layer with a thickness of 500 nm prepared by multiple scraping, Rq=1.25 nm; Figure 8 The absorption curves at different positions on the active layer with a thickness of 100-500 nm prepared by one scraping and multiple scraping in Example 1 of the present invention; wherein, (a) is an absorption curve at different positions on the active layer with a thickness of 100 nm prepared by one scraping, (b) is an absorption curve at different positions on the active layer with a thickness of 300 nm prepared by one scraping, (c) is an absorption curve at different positions on the active layer with a thickness of 500 nm prepared by one scraping, (d) is an absorption curve at different positions on the active layer with a thickness of 100 nm prepared by multiple scraping, (e) is an absorption curve at different positions on the active layer with a thickness of 300 nm prepared by multiple scraping, and (f) is an absorption curve at different positions on the active layer with a thickness of 500 nm prepared by multiple scraping; Fig. 9 The graphs are graphs showing the change of fluorescence spectral characteristics over time during the drying process of the active layer with a thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1 of the present invention; wherein, (a) is a graph showing the change of fluorescence intensity over time during the drying process of the active layer with a thickness of 100-500 nm prepared by single scraping, (b) is a graph showing the change of fluorescence intensity over time during the drying process of the active layer with a thickness of 100-500 nm prepared by multiple scraping, (c) is a graph showing the change of fluorescence peak position over time during the drying process of the active layer with a thickness of 100-500 nm prepared by single scraping, and (d) is a graph showing the change of fluorescence peak position over time during the drying process of the active layer with a thickness of 100-500 nm prepared by multiple scraping. DETAILED DESCRIPTION

[0021] Terminology explanation: PM6 is a polymer photovoltaic material, mainly used as a donor material for organic solar cells.

[0022] L8-BO is a non-fullerene small molecule photovoltaic material, mainly used as an acceptor material for organic solar cells.

[0023] PNDIT-F3N-Br is a polymer photovoltaic material, mainly used as an electron transport layer material for organic solar cells.

[0024] PEDOT:PSS is a conductive polymer composite material, mainly used as a hole transport layer material for organic solar cells.

[0025] The maximum thickness refers to the thickness of the active layer in the organic solar cell. The thickness of the active layer in the organic solar cell provided by the present invention can reach 500 nm.

[0026] In view of the problem that the method of increasing the concentration of the active layer solution to prepare thick organic solar cells is limited by the solubility of the organic material, which can easily cause uneven active layers and affect the performance of the organic solar cells, the present invention provides a method for preparing thick organic solar cells based on multilayer coating.

[0027] A typical embodiment of the present invention provides a thick organic solar cell based on multi-layer coating, which structurally comprises: conductive glass, a hole transport layer, an active layer, an electron transport layer and a metal electrode; The thickness of the active layer is 100-500 nm.

[0028] The present invention can regulate the micro-nanostructure and film-forming dynamics of the active layer of the organic solar cell to prepare an organic solar cell with an active layer thickness of 500 nm. The energy conversion efficiency of the organic solar cell is at the leading level among the organic solar cells currently prepared by halogen-free solvent processing.

[0029] The present invention does not impose any requirements on the thickness of the conductive glass, hole transport layer, electron transport layer and metal electrode in the organic solar cell, and conventional thicknesses in the field of organic solar cells may be used.

[0030] In some examples of this implementation, the conductive glass is indium tin oxide conductive glass, the hole transport layer material is PEDOT:PSS, the donor of the active layer material is PM6, the acceptor is L8-BO, the donor-acceptor mass ratio is 1:1.1-1.3, the electron transport layer material is PNDIT-F3N-Br, and the metal electrode is a silver electrode.

[0031] Another typical embodiment of the present invention provides a method for preparing a thick organic solar cell based on multilayer coating, comprising the following steps: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; In an air atmosphere, the active layer material is scraped on the hole transport layer multiple times, the concentration of the active layer material solution is 8-20 mg / mL, the scraping speed is 10-45 mm / s, the amount of liquid dropped once is 20-90 μL, the substrate temperature is 40-100°C, and the active layer with a thickness range of 100-500 nm is obtained; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a cathode is prepared on the electron transport layer to obtain a thick organic solar cell based on multilayer coating.

[0032] The present invention selects the polymer donor PM6 with relatively high energy conversion efficiency and the non-fullerene small molecule acceptor L8-BO as the active layer material system, and prepares the photosensitive active layer with a thickness range of 100-500 nm by one or more spin coating and one or more air scraping respectively. The crystallinity of the active layer prepared by multiple spin coating is significantly reduced compared with the active layer prepared by one spin coating, which has an adverse effect on the performance of the organic solar cell, while the active layer prepared by multiple scraping not only has greatly improved uniformity, but also has significantly enhanced molecular crystallization. The energy conversion efficiency of the organic solar cell prepared by the method described in the present invention (diluted solution, multiple scraping) is equivalent to that of the one scraping, and the uniformity of the filling factor is greatly improved. The energy conversion efficiency of the organic solar cell with an active layer thickness of 500 nm is at the leading level among the devices currently prepared by halogen-free solvent processing.

[0033] In some examples of this implementation, the conductive glass is indium tin oxide conductive glass, which is ultrasonically cleaned with deionized water, acetone, anhydrous ethanol and isopropanol in sequence, blown dry with nitrogen, treated with ultraviolet light (UV) for 15-25 min, and then spin-coated to prepare a hole transport layer.

[0034] The UV treatment time is preferably 15 min.

[0035] In some examples of this embodiment, the hole transport material is PEDOT:PSS, and PEDOT:PSS is spin-coated on the surface of the conductive glass at a spin-coating speed of 3000-5000 rpm for 30-50 s, and annealed at 130-180° C. for 10-20 min to obtain a hole transport layer.

[0036] When PEDOT:PSS is spin-coated on the surface of the conductive glass, the spin-coating speed is preferably 4000 rpm, the spin-coating time is preferably 50 s, and annealing is performed at 150° C. for 10 min to obtain a hole transport layer.

[0037] In some examples of this embodiment, in an air atmosphere, when an active layer with a thickness of 100 nm is prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution is 9.9 mg / mL, the scraping speed is 30 mm / s, the amount of liquid dropped at one time is 30 μL, the substrate temperature is 80° C., and the scraping is performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 300 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 13.9 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 500 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 17.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; The scraping is performed 1-5 times, the second scraping direction is opposite to the first scraping direction, the third scraping direction is opposite to the second scraping direction, and so on.

[0038] Preferably, when the number of scraping is 2 times, the performance of the organic solar cell is the best. The performance parameters of the organic solar cell obtained by scraping 1-5 times are shown in Table 1.

[0039] During the scraping process, as the amount of solution in front of the scraper decreases, the thickness of the active layer changes accordingly. Changing the second scraping direction can largely solve this problem and improve the uniformity of the active layer.

[0040] In some examples of this implementation manner, the solvent of the active layer material solution is one of chloroform, o-xylene or toluene, the donor of the active layer material is PM6, the acceptor is L8-BO, and the donor-acceptor mass ratio is 1:1.1-1.3.

[0041] Preferably, the solvent of the active layer material solution is o-xylene, and the donor-acceptor mass ratio is 1:1.2.

[0042] In some examples of this embodiment, after the scraping is completed, annealing is performed at 95-105° C. for 8-12 min in an inert atmosphere to obtain an active layer with a thickness ranging from 100-500 nm.

[0043] Preferably, after the coating is completed, annealing is performed at 100° C. for 10 min in an inert atmosphere.

[0044] In some examples of this embodiment, the method for preparing the electron transport layer comprises the following steps: Under nitrogen atmosphere, 0.5-1.5 mg / mL PNDIT-F3N-Br solution was spin-coated onto the active layer at a spin-coating speed of 2000-4000 rpm for 30-50 s.

[0045] Preferably, under a nitrogen atmosphere, a 1.5 mg / mL PNDIT-F3N-Br solution is spin-coated onto the active layer at a spin-coating speed of 3000 rpm for 30 s.

[0046] In some examples of this embodiment, the solvent of the PNDIT-F3N-Br solution is methanol.

[0047] In some examples of this embodiment, the method for preparing the metal electrode comprises the following steps: Silver electrodes with a thickness of 80-100 nm were prepared on the electron transport layer by thermal evaporation under vacuum conditions.

[0048] In some examples of this embodiment, the vacuum condition is 2.5×10 -4 -5×10 -4 Pa.

[0049] Wherein, the vacuum condition is preferably 4×10 -4 Pa.

[0050] In contrast to the preparation method of the present invention, the present invention also provides a preparation method of a thick organic solar cell based on one-time scraping, comprising the following steps: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; In an air atmosphere, the active layer material is scraped once on the hole transport layer, the concentration of the active layer material solution is 15-30 mg / mL, the scraping speed is 10-45 mm / s, the amount of liquid dropped once is 20-90 μL, the substrate temperature is 40-100°C, and the active layer with a thickness range of 100-500 nm is obtained; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a cathode is prepared on the electron transport layer to obtain a thick organic solar cell based on multilayer coating.

[0051] Preferably, in an air atmosphere, when a 100 nm active layer is prepared by scraping at one time, the concentration of the active layer material solution is 18.7 mg / mL, the scraping speed is 30 mm / s, the drop volume is 30 μL at one time, and the substrate temperature is 80°C; In air atmosphere, when a 300 nm active layer was prepared by scraping once, the concentration of the active layer material solution was 26.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, and the substrate temperature was 80°C. In an air atmosphere, when a 500 nm active layer was prepared by scraping in one time, the concentration of the active layer material solution was 39.6 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, and the substrate temperature was 80°C.

[0052] In contrast to the preparation method of the present invention, the present invention also provides a preparation method of a thick organic solar cell based on one-time spin coating, and the specific steps are as follows: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; Spin coating the active layer material once on the hole transport layer, the concentration of the active layer material solution is 15-40 mg / mL, the spin coating speed is 2000-4000 rpm, the spin coating time is 30-40 s, and the active layer with a thickness range of 100-500 nm is prepared; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a cathode is prepared on the electron transport layer to obtain a thick organic solar cell based on multilayer coating.

[0053] Preferably, when a 100 nm thick active layer is prepared by spin coating once, the concentration of the active layer material solution is 16.5 mg / mL, the spin coating speed is 4000 rpm, and the time is 30 s; When a 300 nm thick active layer was prepared by spin coating once, the concentration of the active layer solution was 26.4 mg / mL, the spin coating speed was 2000 rpm, and the time was 40 s; When a 500 nm thick active layer was prepared by spin coating once, the concentration of the active layer solution was 39.6 mg / mL, the spin coating speed was 2000 rpm, and the time was 40 s.

[0054] In contrast to the preparation method of the present invention, the present invention also provides a preparation method of a thick organic solar cell based on multiple spin coatings, and the specific steps are as follows: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; Spin coating the active layer material on the hole transport layer multiple times, the concentration of the active layer material solution is 5-20 mg / mL, the spin coating speed is 2000-4000 rpm, the spin coating time is 30-40 s, and the spin coating is performed 1-5 times to prepare an active layer with a thickness range of 100-500 nm; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a cathode is prepared on the electron transport layer to obtain a thick organic solar cell based on multiple spin coating.

[0055] Preferably, when the active layer with a thickness of 100 nm is prepared by multiple spin coating, the concentration of the active layer solution is 7.7 mg / mL, the spin coating speed is 4000 rpm, the time is 30 s, and the spin coating is 3 times; When the active layer with a thickness of 300 nm was prepared by multiple spin coating, the concentration of the active layer solution was 14.3 mg / mL, the spin coating speed was 2000 rpm, the time was 40 s, and the spin coating was 3 times; When the active layer with a thickness of 500 nm was prepared by multiple spin coating, the concentration of the active layer solution was 20.9 mg / mL, the spin coating speed was 2000 rpm, the time was 40 s, and the spin coating was performed 3 times.

[0056] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0057] Example 1 A method for preparing a thick organic solar cell (active layer thickness of 100-500 nm) based on double scraping, comprising the following steps: like Figure 1 As shown, an organic solar cell with the same active layer thickness range is prepared by a one-time scraping method for comparison, and the selected materials and preparation steps are as follows: The donor and acceptor in the active layer are PM6 and L8-BO respectively, and the donor-acceptor mass ratio is 1:1.2. The substrate is a glass substrate, the anode is indium tin oxide (ITO) conductive glass, and the material of the hole transport layer is PEDOT:PSS. The material of the electron transport layer is PNDIT-F3N-Br. The cathode is the top metal Ag electrode. The upper right corner of the back of the glass substrate is engraved with a mark.

[0058] (1) The ITO conductive glass was ultrasonically cleaned with deionized water, acetone, anhydrous ethanol and isopropanol in sequence, dried with nitrogen, and then treated with UV for 15 min. (2) In air atmosphere, PEDOT:PSS was spin-coated on the surface of ITO conductive glass at a speed of 4000 rpm for 50 s and annealed at 150 °C for 10 min to obtain a hole transport layer. (3) Preparing an active layer by scraping on the surface of the hole transport layer, including: In an air atmosphere, when an active layer with a thickness of 100 nm was prepared by scraping in one time, the concentration of the active layer material solution (solvent is o-xylene) was 18.7 mg / mL, the scraping speed was 30 mm / s, the drop volume was 30 μL, and the substrate temperature was 80°C.

[0059] In an air atmosphere, when a 300 nm thick active layer was prepared by scraping in one time, the concentration of the active layer material solution (solvent: o-xylene) was 26.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, and the substrate temperature was 80°C.

[0060] In an air atmosphere, when a 500 nm thick active layer was prepared by scraping in one time, the concentration of the active layer material solution (solvent: o-xylene) was 39.6 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, and the substrate temperature was 80°C.

[0061] In air atmosphere, when the active layer with a thickness of 100 nm was prepared by two scrapings, the concentration of the active layer material solution (solvent is o-xylene) was 9.9 mg / mL, the scraping speed was 30 mm / s, the drop volume was 30 μL, and the substrate temperature was 80°C. The second scraping was performed in the opposite direction to the first scraping.

[0062] In an air atmosphere, when the active layer with a thickness of 300 nm was prepared by two scrapings, the concentration of the active layer material solution (solvent is o-xylene) was 13.9 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, and the substrate temperature was 80°C. The second scraping was performed in the opposite direction to the first scraping.

[0063] In an air atmosphere, when the active layer with a thickness of 500 nm was prepared by two scrapings, the concentration of the active layer material solution (solvent is o-xylene) was 17.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, and the substrate temperature was 80°C. The second scraping was performed in the opposite direction to the first scraping.

[0064] After the coating was completed, the active layers with thicknesses of 100, 300, and 500 nm were prepared by annealing at 100°C for 10 min in an inert atmosphere.

[0065] (4) Spin coating an electron transport layer on the surface of the active layer, comprising: 1.5 mg / mL PNDIT-F3N-Br solution was spin-coated onto the active layer at a speed of 3000 rpm for 30 s.

[0066] (5) Preparing a cathode on the electron transport layer under vacuum conditions, including: In 4×10 -4 The Ag electrode with a thickness of 100 nm was prepared by thermal evaporation under a vacuum condition of 0.03 Pa. Comparative Example 1 A method for preparing organic solar cells with a wide thickness range (active layer thickness of 100-500 nm) based on one or more spin coatings comprises the following steps: As shown in FIG2 , an organic solar cell with the same active layer thickness range is prepared by one or more spin coating methods for comparison. The materials and preparation steps are as shown in Example 1. The difference from Example 1 is that step (3) is different. The specific content of step (3) of this comparative example 1 is as follows, and the rest of the content is consistent with that of Example 1. (3) Spin coating the active layer on the surface of the hole transport layer, comprising: When a 100 nm thick active layer was prepared by spin coating once, the concentration of the active layer solution (the solvent was chloroform) was 16.5 mg / mL, the spin coating speed was 4000 rpm, and the time was 30 s.

[0067] When a 300 nm thick active layer was prepared by spin coating once, the concentration of the active layer solution (the solvent was chloroform) was 26.4 mg / mL, the spin coating speed was 2000 rpm, and the time was 40 s.

[0068] When a 500 nm thick active layer was prepared by spin coating once, the concentration of the active layer solution (the solvent was chloroform) was 39.6 mg / mL, the spin coating speed was 2000 rpm, and the time was 40 s.

[0069] When the active layer with a thickness of 100 nm was prepared by multiple spin coating, the concentration of the active layer solution (the solvent was chloroform) was 7.7 mg / mL, the spin coating speed was 4000 rpm, the time was 30 s, and the spin coating was performed 3 times.

[0070] When the active layer with a thickness of 300 nm was prepared by multiple spin coating, the concentration of the active layer solution (the solvent was chloroform) was 14.3 mg / mL, the spin coating speed was 2000 rpm, the time was 40 s, and the spin coating was performed 3 times.

[0071] When the active layer with a thickness of 500 nm was prepared by multiple spin coating, the concentration of the active layer solution (the solvent was chloroform) was 20.9 mg / mL, the spin coating speed was 2000 rpm, the time was 40 s, and the spin coating was performed 3 times.

[0072] After spin coating, the active layers with thicknesses of 100 nm, 300 nm, and 500 nm were prepared by annealing at 100°C for 10 min in an inert atmosphere.

[0073] Comparative Example 2 A method for preparing an organic solar cell based on multi-layer scraping / spin coating comprises the following steps: Organic solar cells with the same active layer thickness range were prepared by multi-layer scraping / spin coating methods for comparison. The materials and preparation steps are as follows: The donor and acceptor in the active layer are PM6 and L8-BO respectively, and the donor-acceptor mass ratio is 1:1.2. The substrate is a glass substrate, the anode is ITO conductive glass, the material of the hole transport layer is PEDOT:PSS, the material of the electron transport layer is PNDIT-F3N-Br, and the cathode is a top metal Ag electrode. (1) The ITO conductive glass was ultrasonically cleaned with deionized water, acetone, anhydrous ethanol and isopropanol in sequence, dried with nitrogen, and then treated with UV for 15 min. (2) In air atmosphere, PEDOT:PSS was spin-coated on the surface of ITO conductive glass at a speed of 4000 rpm for 50 s and annealed at 150 °C for 10 min to obtain a hole transport layer. (3) Preparing an active layer on the surface of the hole transport layer, comprising: In air atmosphere, when scraping each active layer, the concentration of the active layer material solution (solvent is o-xylene) is 9.9 mg / mL, the scraping speed is 30 mm / s, the drop volume is 30 μL, and the substrate temperature is 80°C. Scrape 1, 2, 3, 4, and 5 layers respectively. The next layer is scraped in the opposite direction of the previous layer.

[0074] After the coating was completed, the active layers with different numbers of layers were prepared by annealing at 100°C for 10 min in an inert atmosphere.

[0075] Alternatively, in a nitrogen atmosphere, when spin coating each active layer, the concentration of the active layer material solution (the solvent is chloroform) is 7.7 mg / mL, the spin coating speed is 4000 rpm, and the time is 30 s. Spin coating 1 layer, 2 layers, 3 layers, 4 layers, and 5 layers respectively.

[0076] After spin coating, the active layers with different numbers of layers were prepared by annealing at 100°C for 10 min in an inert atmosphere.

[0077] (4) Spin coating an electron transport layer on the surface of the active layer, comprising: 1.5 mg / mL PNDIT-F3N-Br solution was spin-coated onto the active layer at a speed of 3000 rpm for 30 s.

[0078] (5) Preparing a cathode on the electron transport layer under vacuum conditions, including: In 4×10 -4The Ag electrode with a thickness of 100 nm was prepared by thermal evaporation under a vacuum condition of 0.03 Pa. Performance Verification Performance parameters of organic solar cells: power conversion efficiency (PCE)

[0079] In the formula J SC is the short-circuit current density, V OC is the open circuit voltage, FF is the fill factor, P in is the incident light power density. J- V The characteristics were tested using a Keithley 2400 source meter. The light source of standard sunlight (AM 1.5 G) was a 3A solar simulator (Sofn Instruments Co. Ltd.), and the light intensity was calibrated by a silicon cell.

[0080] The performance parameters of the organic solar cell prepared by multi-layer blade coating / spin coating in Comparative Example 2 are shown in Table 1.

[0081] Table 1 Performance parameters of multilayer scraping / spin coating organic solar cells

[0082] It can be seen from Table 1 that when the number of active layers is 2, the performance of the organic solar cell obtained by multiple scraping is the best, and when the number of active layers is 3, the performance of the organic solar cell obtained by multiple spin coating is the best.

[0083] Figure 3 (a) is the energy conversion efficiency of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1, Figure 3 (b) is the filling factor of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1, Figure 3 (c) is the open circuit voltage of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1, Figure 3 (d) is the short-circuit current density of the organic solar cell with an active layer thickness of 100-500 nm prepared by single scraping and multiple scraping in Example 1. Figure 4 (a) is the energy conversion efficiency of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1, Figure 4 (b) is the filling factor of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1, Figure 4(c) is the open circuit voltage of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1, Figure 4 (d) is the short-circuit current density of the organic solar cell with an active layer thickness of 100-500 nm prepared by single spin coating and multiple spin coating in Comparative Example 1. See Table 2 for specific data.

[0084] Table 2 Performance parameters of organic solar cells

[0085] pass Figure 3 and Figure 4 As shown in Table 2, the performance of the organic solar cell obtained by multiple spin coating is lower than that of the single spin coating under the same active layer thickness, while the performance of the organic solar cell obtained by multiple scraping coating is equivalent to that of the single scraping coating, indicating that scraping coating is more suitable for the dilution solution and multiple coating preparation method proposed in the present invention. Table 2 shows that the performance of the organic solar cell is the best when scraping twice.

[0086] Figure 5 (a) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of an active layer with a thickness of 500 nm prepared by one-time scraping in Example 1, Figure 5 (b) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of an active layer with a thickness of 500 nm prepared by multiple scraping in Example 1, Figure 5 (c) is a one-dimensional integral curve diagram of an active layer with a thickness of 500 nm prepared by one-time scraping and an active layer with a thickness of 500 nm prepared by multiple scraping in Example 1, Figure 6 (a) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of an active layer with a thickness of 500 nm prepared by one-time spin coating in Comparative Example 1, Figure 6 (b) is a two-dimensional grazing incidence wide-angle X-ray diffraction pattern of an active layer with a thickness of 500 nm prepared by multiple spin coating in Comparative Example 1, Figure 6 (c) is a one-dimensional integral curve of the active layer with a thickness of 500 nm prepared by single spin coating and the active layer with a thickness of 500 nm prepared by multiple spin coating in Comparative Example 1. It can be seen that the molecular stacking of active layers of different thicknesses is face-up, which is conducive to the extraction of carriers. Compared with the active layer prepared by multiple spin coating, the active layer prepared by the preparation method of multiple scraping can enhance its crystallinity without destroying the orderly stacking of molecules.

[0087] Figure 7 (a) is an atomic force microscope image of an active layer with a thickness of 100 nm prepared by one-time scraping in Example 1, Rq=1.26 nm; Figure 7(b) is an atomic force microscope image of an active layer with a thickness of 300 nm prepared by one-time scraping in Example 1, Rq=1.30 nm; Figure 7 (c) is an atomic force microscope image of an active layer with a thickness of 500 nm prepared by one-time scraping in Example 1, Rq=1.35 nm; Figure 7 (d) is an atomic force microscope image of an active layer with a thickness of 100 nm prepared by multiple scraping in Example 1, Rq=0.86 nm; Figure 7 (e) is an atomic force microscope image of an active layer with a thickness of 300 nm prepared by multiple scraping in Example 1, Rq=1.04 nm; Figure 7 (f) is an atomic force microscope image of an active layer with a thickness of 500 nm prepared by multiple scraping in Example 1, Rq=1.25 nm, all active layers show similar surface morphology, and as the thickness of the active layer increases, the surface roughness increases. In addition, the roughness of the active layer prepared by diluting the solution and multiple scraping is correspondingly smaller, showing a more ideal surface morphology.

[0088] Figure 8 (a) is an absorption curve diagram of different positions on the active layer with a thickness of 100 nm prepared by one-time scraping in Example 1, Figure 8 (b) is an absorption curve diagram of different positions on the active layer with a thickness of 300 nm prepared by one-time scraping in Example 1, Figure 8 (c) is an absorption curve diagram of different positions on the active layer with a thickness of 500 nm prepared by one-time scraping in Example 1, Figure 8 (d) is an absorption curve diagram of different positions on the active layer with a thickness of 100 nm prepared by multiple scraping in Example 1. Figure 8 (e) is an absorption curve diagram of different positions on the active layer with a thickness of 300 nm prepared by multiple scraping in Example 1. Figure 8 (f) is the absorption curve at different positions on the active layer with a thickness of 500 nm prepared by multiple scraping in Example 1. It can be clearly seen that the distribution range of the absorption peak intensity of the active layer obtained by diluting the solution and scraping multiple times is narrower. During the scraping process, as the amount of solution in front of the scraper decreases, the thickness of the active layer changes accordingly. The second scraping of the diluting solution and the second scraping adopts the scraping direction opposite to the first scraping, which can largely solve this problem and has a significant advantage in the uniformity of the active layer.

[0089] Fig. 9 (a) is a graph showing the change in fluorescence intensity over time during the drying process of the active layer with a thickness of 100-500 nm prepared by one-time scraping in Example 1. Fig. 9(b) is a graph showing the change in fluorescence intensity over time during the drying process of the active layer with a thickness of 100-500 nm prepared by multiple scraping in Example 1. Fig. 9 (c) is a graph showing the change of the fluorescence peak position over time during the drying process of the active layer with a thickness of 100-500 nm prepared by one-time scraping in Example 1, Fig. 9 (d) in the figure is a graph showing the change of the fluorescence peak position over time during the drying process of the active layer with a thickness of 100-500 nm prepared by multiple scraping in Example 1. The change in fluorescence intensity in the in-situ test can reflect the fluorescence quenching caused by aggregation during the transition from the solution state to the aggregated state in the active layer. It can be seen that as the thickness of the active layer increases, the decay of the fluorescence intensity slows down and the drying time of the active layer increases. For the active layer prepared by one scraping, the decay time increases from about 1 s for 100 nm to about 2.5 s for 500 nm. Regardless of whether it is one scraping or a diluted solution or two scrapings, the changes in the receptor peak position before and after film formation are not significantly different in active layers of different thicknesses.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thick organic solar cell based on multilayer coating, characterized in that: Its structure includes: conductive glass, hole transport layer, active layer, electron transport layer and metal electrode; The thickness of the active layer is 100-500 nm.

2. The thick organic solar cell based on multi-layer coating as claimed in claim 1, characterized in that: The conductive glass is indium tin oxide conductive glass, the hole transport layer material is PEDOT:PSS, the donor of the active layer material is PM6, the acceptor is L8-BO, the donor-acceptor mass ratio is 1:1.1-1.3, the electron transport layer material is PNDIT-F3N-Br, and the metal electrode is a silver electrode.

3. A method for preparing a thick organic solar cell based on multilayer coating according to claim 1 or 2, characterized in that: The steps include: In an air atmosphere, a hole transport material is spin-coated on the surface of a conductive glass to prepare a hole transport layer; In an air atmosphere, the active layer material is scraped on the hole transport layer multiple times, the concentration of the active layer material solution is 8-20 mg / mL, the scraping speed is 10-45 mm / s, the amount of liquid dropped once is 20-90 μL, the substrate temperature is 40-100°C, and the active layer with a thickness range of 100-500 nm is obtained; In a nitrogen atmosphere, spin coating an electron transport layer material on the surface of the active layer to prepare an electron transport layer; Under vacuum conditions, a metal electrode is prepared on the electron transport layer to obtain a thick organic solar cell based on multilayer coating.

4. The method for preparing a thick organic solar cell based on multilayer coating according to claim 3, characterized in that: The conductive glass is indium tin oxide conductive glass, which is ultrasonically cleaned with deionized water, acetone, anhydrous ethanol and isopropanol in sequence, blown dry with nitrogen, treated with ultraviolet light for 15-25 minutes, and then spin-coated to prepare a hole transport layer; The hole transport material is PEDOT:PSS, and PEDOT:PSS is spin-coated on the surface of the conductive glass at a spin-coating speed of 3000-5000 rpm for 30-50 s, and annealed at 130-180°C for 10-20 min to obtain a hole transport layer.

5. The method for preparing a thick organic solar cell based on multi-layer coating according to claim 3, characterized in that: In an air atmosphere, when the active layer with a thickness of 100 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 9.9 mg / mL, the scraping speed was 30 mm / s, the amount of liquid dropped at one time was 30 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 300 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 13.9 mg / mL, the scraping speed was 30 mm / s, the drop volume was 50 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; In an air atmosphere, when the active layer with a thickness of 500 nm was prepared by multiple scraping on the hole transport layer, the concentration of the active layer material solution was 17.4 mg / mL, the scraping speed was 30 mm / s, the drop volume was 80 μL, the substrate temperature was 80°C, and the scraping was performed 1-5 times; The scraping is performed 1-5 times, the second scraping direction is opposite to the first scraping direction, the third scraping direction is opposite to the second scraping direction, and so on.

6. The method for preparing a thick organic solar cell based on multilayer coating according to claim 3, characterized in that: The solvent of the active layer material solution is one of chloroform, o-xylene or toluene, the donor of the active layer material is PM6, the acceptor is L8-BO, and the donor-acceptor mass ratio is 1:1.1-1.3; After the coating is completed, annealing is performed at 95-105°C for 8-12 min in an inert atmosphere to obtain an active layer with a thickness ranging from 100 to 500 nm.

7. The method for preparing a thick organic solar cell based on multi-layer coating according to claim 3, characterized in that: The method for preparing the electron transport layer comprises the following steps: Under nitrogen atmosphere, 0.5-1.5 mg / mL PNDIT-F3N-Br solution was spin-coated onto the active layer at a speed of 2000-4000 rpm for 30-50 s.

8. The method for preparing a thick organic solar cell based on multi-layer coating according to claim 7, characterized in that: The solvent of the PNDIT-F3N-Br solution is methanol.

9. The method for preparing a thick organic solar cell based on multi-layer coating according to claim 3, characterized in that: The method for preparing the metal electrode comprises the following steps: Metal electrodes with a thickness of 80-100 nm were prepared on the electron transport layer by thermal evaporation under vacuum conditions.

10. The method for preparing a thick organic solar cell based on multi-layer coating according to claim 3, characterized in that: The vacuum condition is 2.5×10 -4 -5×10 -4 Pa.

Citation Information

Patent Citations

  • Organic photovoltaic device structure based on gradient active layer thickness and preparation method thereof

    CN117479555A